EFFECT OF VITAMIN D SUPPLEMENTATION ON HEPATIC FUNCTION, LIPID PROFILE, AND DIABETIC PROFILE IN STREPTOZOTOCIN-INDUCED DIABETIC RATS (Journal of Pharmaceutical Negative Results, 2022)
Non-alcoholic fatty liver disease (NAFLD) is considered one of the leading liver disorders in type 2 diabetes mellitus (T2DM). The progression of NAFLD is faster in T2DM patients than in nondiabetic patients, consequently leading to serious complications such as cirrhosis and hepatocarcinoma. vitamin D3 has been reported to protect the liver from non-alcoholic fatty liver disease (NAFLD) by attenuating liver damage in type 2 diabetes mellitus (T2DM). vitamin D3 also regulates inflammation by reducing the release of pro-inflammatory cytokines and affects insulin action and lipid metabolism. The present study evaluates the role of vitamin D3 in protecting the liver in NAFLD. In the present study, rats were injected intraperitoneally with 30 mg/kg of streptozotocin and fed a high-fat diet to induce diabetes. All rats were administered vehicle or vitamin D3 (300 ng/kg and 600 ng/kg) by oral gavage for 4 weeks. To assess the status of liver Alanine transaminase, Aspartate transaminase was estimated other parameters such as blood glucose, and vitamin D3 lipid profiles were done. Results showed vitamin D3 treatment improved insulin resistance, liver damage and plasma lipid profiles and in diabetic rats. Finally, the present study provides evidence that vitamin D3 could improve dyslipidemia and prevent NAFLD in T2DM.